Let´s Swing it –The Interaction Between Participation-Related Shoulder Load and Pre-season Trunk Rotation Power on Shoulder Problems in Male Handball Players - Kari Arnason; Atli Agustsson; Hilde Fredriksen; Elis Thor Rafnsson; Kristin Briem (International Journal of Sports Physical Therapy)
# Background